Micro:bit for mad scientists 30 clever coding and electronics projects for kids - Monk, Simon (No Starch Press, 2019)
"A beginner-friendly collection of electronics projects for the Micro:bit. Teaches how to code in MicroPython and JavaScript Blocks, as well as how to build specific mad scientist themed projects such as a magnetic door alarm, a lie detector, and an irregular wall clock"--
Description based on online resource; title from digital title page (viewed on May 07, 2020)
Keywords: Micro:bit -- Juvenile literature; Single-board computers -- Juvenile literature; Electronics -- Juvenile literature -- Data processing; Python (Computer program language) -- Juvenile literature; JavaScript (Computer program language) -- Juvenile literature; Électronique; Informatique; Ouvrages pour la jeunesse; Python (Langage de programmation); Ouvrages pour la jeunesse; JavaScript (Langage de programmation); Ouvrages pour la jeunesse; Electronics; Data processing; JavaScript (Computer program language); Micro:bit; Python (Computer program language); Single-board computers; Juvenile works